Sensitivities to surfactants in Desmodesmus subspicatus, Daphnia galeata, and Bosmina longirostris - Miyabara, Yuichi; Oda, Yusuke (Japanese Journal of Environmental Toxicology, 2022)
We performed algal growth inhibition test on Desmodesmus subspicatus using a cationic surfactant benzalkonium bromide (BZK-Br), and acute toxicity tests on two cladoceran species, Daphnia galeata and Bosmina longirostris, using BZK-Br and an anionic surfactant sodium octyl sulfate (SOS). The 72-h 50% effective concentration (EC50) with 95% confidence interval (CI) of initial BZK-Br to D. subspicatus was 60.3 µg L−1 with 46.4–74.2 µg L−1. The 48-h EC50s (with those CIs) of BZK-Br to D. galeata and B. longirostris, estimated from the geometric mean concentrations, were 40.9 (33.0–48.8) µg L−1 and 80.1 (68.1–92.0) µg L−1, respectively. Unlike BZK-Br, the 48-h EC50s (with those CIs) of SOS to D. galeata (335.9 mg L−1, 248.5–423.3 mg L−1) and B. longirostris (280.0 mg L−1, 211.1–348.9 mg L−1) were comparable. The present results were discussed about the difference in EC50s to similar compounds on standard test organisms. We also mentioned that BZK-Br and SOS concentrations can present below the EC50s in surface water, whereas they can affect biological interactions by interfering with colony formation response in D. subspicatus even at environmentally relevant concentrations.